2021
DOI: 10.1038/s41598-021-84587-x
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term exposure to air pollution increases the risk of ischemic heart disease

Abstract: Previous studies have suggested an increased risk of ischemic heart disease related to air pollution. This study aimed to explore both the short-term and long-term effects of air pollutants on the risk of ischemic heart disease after adjusting for meteorological factors. The Korean National Health Insurance Service-Health Screening Cohort from 2002 to 2013 was used. Overall, 2155 participants with ischemic heart disease and 8620 control participants were analyzed. The meteorological data and air pollution data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
(45 reference statements)
3
18
0
Order By: Relevance
“…In 2019, nearly 3 billion people worldwide lean upon polluting fuels with poor ventilation and incomplete combustion for household purposes 9 . It has been documented that particulate air pollution is correlated with a higher risk of IHD hospitalization and death 10–15 . The global, regional, and national burden of IHD attributed to HAP are still unclear over past decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, nearly 3 billion people worldwide lean upon polluting fuels with poor ventilation and incomplete combustion for household purposes 9 . It has been documented that particulate air pollution is correlated with a higher risk of IHD hospitalization and death 10–15 . The global, regional, and national burden of IHD attributed to HAP are still unclear over past decades.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been documented that particulate air pollution is correlated with a higher risk of IHD hospitalization and death. [10][11][12][13][14][15] The global, regional, and national burden of IHD attributed to HAP are still unclear over past decades. Therefore, it is particularly valuable to develop targeted strategies for HAP-related IHD according to its spatial and temporal patterns in reducing the IHD burden.…”
Section: Introductionmentioning
confidence: 99%
“…Deterioration of air quality has become one of the largest challenges to human development, posing a major threat to the human body and hence significantly enhancing the health consensus of the public: the air quality in the living areas must be beneficial to the human body [1][2][3][4]. Comparing with the atmospheric environment, the significance of protecting the indoor air quality should be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) report demonstrated that respiratory diseases caused by air pollution in 2019 ranked fourth in the top 10 causes of death worldwide ( (accessed on 15 July 2021)). Numerous studies have verified that short-term or long-term exposure to air pollutants, including PM 2.5 , PM 10 , NO 2 , and SO 2, increased the risks of mortality and morbidity, thereby posing a severe threat to the public health of the residents [ 5 ]. As an important part of the urban ecosystem, in addition to providing residents with green spaces for recreation and entertainment, urban green spaces also improve air quality.…”
Section: Introductionmentioning
confidence: 99%